"But I just want a book!" Is your discovery layer meeting your users' needs?. Issue 4 (2nd October 2018) - Rigda, Christine; Hoogland, Margaret; Morales, Jessica
Abstract: In January 2016, the University of Toledo Libraries implemented EBSCO Discovery Services (EDS) as its discovery layer. Administrators questioned whether users were able to find consortial material in the EDS, so they assembled a task force to conduct a pilot usability test. The task force gathered demographic data and recorded the screens of 25 students answering six task questions. Results showed participants could easily find most items except books, and for tasks that were open-ended, many students continued searching even though they found relevant material. To determine why participants could not find books, the task force consulted with EBSCO and discovered a configuration problem that was easily resolved by editing a mapping table and adding a custom limiter for print books. The searching issue was more difficult to determine, and the task force suggests a lack of library instruction may be at least partly to blame. Libraries invest significant resources in discovery layers. If users have difficulty using them or finding relevant material for their assignments, libraries need to address that issue and instruction is one solution. This pilot study reports on what the University Libraries did to make the EDS more usable for its users.